Association between RELN polymorphisms and schizophrenia in a Han population from Northeast China. (December 2019) - Bai, Wei; Fu, Yingli; Yu, Xiao; Zhu, Bo; Duan, Ruixin; Yu, Yaqin; Kou, Changgui
Abstract : Objective: To explore the association between the RELN gene and schizophrenia in the overall sample and samples stratified by sex in a northeastern Chinese population. Methods: A total of 1536 participants from Jilin Province, China, were recruited in this case-control study. Four single nucleotide polymorphisms (rs1062831, rs3808039, rs362746, and rs736707) in the RELN gene were genotyped. Binary logistic regression analysis was applied to detect associations between the genotypes of each single nucleotide polymorphism and schizophrenia. P values of no more than 0.003125 [0.05/(4 SNPs*4 different genetic models)] after Bonferroni correction were considered statistically significant. Results: All single-nucleotide polymorphisms conformed to Hardy–Weinberg equilibrium in the control group. Logistic regression analysis revealed that after Bonferroni correction, rs362746 was associated with schizophrenia under the recessive model ( P = 0.001) and codominant model ( P = 0.003) in the overall group. The association between schizophrenia and RELN single-nucleotide polymorphisms was not found in a sex-specific pattern after Bonferroni correction. Conclusion: Our study provides and supports the evidence that RELN is a candidate gene for schizophrenia. Replication studies conducted in different populations are required, and the sex-specific association of this gene with schizophrenia warrants further exploration.